Gambaran Kepatuhan Mengkonsumsi Tablet Zat Besi (Fe) dan Konsumsi Zat Besi Dengan Status Anemia Gizi Pada Ibu Hamil Di Wilayah Kerja UPTD Puskesmas IV Denpasar Selatan - Kusuma Dewi, Kadek Pande; Suarjana, SKM., M.Kes, I Made; Wiardani, SST., M.Kes, Dr. Ni Komang (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Based on 2018 Riskesdas data, it shows that the prevalence of anemia in pregnant women in Indonesia is 48.9%, an increase of 11% compared to 2013 Riskesdas data, which was 37.1%. Based on 2020 Bali Provincial Health Office data, it shows that the incidence of anemia in 2019 was 5.07%, then increased to 5.78% in 2020. Meanwhile, the incidence of anemia in Denpasar City in 2019 was 4.7%, increasing to 7. 55% in 2020. The highest coverage of iron tablets in Bali Province is in Denpasar City with a percentage of 98.5% in 2021. This research aims to determine the fulfillment of consuming iron (Fe) tablets and iron consumption by nutritional anemia status in pregnant women in the working area of UPTD Puskesmas IV South Denpasar. This type of research is classified as observational research with a cross sectional design. This research started from mid-April to mid-May 2024. The sample for this research was 44 people using purposive sampling techniques in sampling. The results of this study showed that 59.1% of pregnant women experienced anemia. 9.1% of pregnant women were non-compliant in consuming iron tablets. 84.1% of pregnant women have insufficient iron consumption. Pregnant women are advised to consume foods that are rich sources of iron, during pregnancy mothers must adhere to the recommendations for consuming iron tablets, and always adopt clean and healthy living habits.